I knew two who said moo : a counting and rhyming book - Barrett, Judi (New York : Atheneum Books for Young Readers, 2000)
Rhyming lines feature the number from one to ten.
Keywords: Counting -- Juvenile literature; English language -- Rhyme -- Juvenile literature